Sentimentos, saberes e fazeres do cuidador principal do idoso com câncer - Vieira, Maria Cristina Umpierrez (2006)
The demographic transistion in the world resulted in the morbi-mortality population profile alterations, characterized for the chronic diseases incidence increase, such as the cancer. The elderly people attacked for this pathology facing losses, not only on the physical and emotional level, but also in the social one, requires greater support and attention from the family. Thus, this study has as objective to understand the main family caretaker representations on the cancer, the care and the elderlies; to identify the related affective aspects with the main family caretaker paper development, as well as identifying his actions when taking care the elderlies at home. It is a qualitative research that used as referencial the social representations theory for considering the necessity of understanding the main catetaker feelings universe, knowledges and actions. The informers were four women who had familiar bond with the elderlies; they had been selected from a cancer clinic handbooks from Guarapuava city, in the state of Parana. The data collection occurred at home from March to November, 2005 period, using as technique the half-structuralized interview and as methodology participant observation that it was developed in four phases: primary or initial observation; initial observation with some participation; participation with some comment and reflexive observation. For data analysis, it was adopted the thematic analysis method proposed for Minayo (1999). The caretakers' participation in several moments of the daily life enabled the comprehension of their perceptions and experiences. The data are presented in three great reflection areas: what the main caretakers think about the elderly cancer carrier care; affective aspects involved in the care and the use of home therapeutic practices. In the first reflection area the process of getting sick was represented from the etiologic caretaker conceptions and from the meanings they were attributed: The cancer as death menace, the human fragility symbol, accumulative losses and the person announcement expression. The meanings attributed to the care were related to the motivation to persevere in the main caretaker role. The elderly was represented from the links established to the caretaker before the getting sick process beginning and afterwards to the independence and autonomy loss. In the second reflection area were identified the difficulties for developing the care and the benefits associated to the main caretaker role. In the last reflection area, it was verified that in the domiciliate context were integrated informal, formal and popular care practices. The study revealed that the representations about the cancer are narrowly related to the domiciliate therapeutic practices and the meanings attributed to the care with the difficulties perception and the benefits associated to the main caretaker role. It was possible to learn that in the domiciliate space are mobilized knowledges from the common sense, religious beliefs and biomedical knowledges. Searching for the different care scenaries integration and perceiving that the formal system comes maintaining in the margin of the domiciliate practices. It was identified the health professionals need of developing the participating and learning capacity in the world of those who cohabit with the cancer, independent from the painful and challenging this situation can seem. The domiciliate care context also shows some ethical challenges to the formal system, because it puts in evidence the family participation importance in the elderly cancer treatment decision , so that the main caretakers think that it is part from their responsibility, on the other hand, they questionate the interpretation from the care supplied by the formal system aims attend to the cancer affected elderlies needs, because in fact, it was verified that the main caretaker needs to search resources in the family, in the community, in the formal and popular system to attend to the demands from an integral care, what reveals that no isolated system reaches this goal.